Things: religion and the question of materiality - Meyer, Birgit; Houtman, Dick (The future of the religious past, 2012)
Focusing on different kinds of things that matter for religion, including sacred artifacts, images, bodily fluids, sites, and electronic media, this volume offers a wide-ranging set of multidisciplinary studies that combine detailed analysis and critical reflection.